Improving Quality of Service Interaction Pattern Related Government, Tourism, and Society - Agus Aprianti; Anisah Firli (Universitas Garut, 2017)
Abstract. Indonesia is an archipelago country that has diverse cultures and plentiful natural resources. There is no denying that this gives a special attraction for local and international tourists to see and witness the event held on the unique culture that spread across regions in Indonesia. In addition to the typical Indonesian cultural event, frequently an important event was also held in Indonesia, both events at regional, national, to international. Event held in Indonesia is also very diverse, such as musical performances, sports, cultural tourism, education, and others. There is a fundamental problem that the pattern of interaction between the government, tourists, and society not yet optimal and this study attempts to explore patterns of interaction between the government, tourists and society; obstacles encountered related patterns of interaction between the government, tourists and society; as well as how to improve the quality of tourism services. The methodology used in conducting this study is to collect data from the literature with a qualitative approach (case study in Lombok Tourism). After discovered the pattern of interaction and how improve the quality of service, the next step will be adopted the concept of social media interaction engineering considerations in the digital age that utilize social media among government, tourists, and society. Keywords : Interaction Pattern; Management, Quality of Service;